2000
DOI: 10.1088/0031-9155/45/8/305
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy planning of the pelvis using distortion corrected MR images: the removal of system distortions

Abstract: Image distortion is an important consideration in the use of magnetic resonance (MR) images for radiotherapy planning. The distortion is a consequence of system distortion (arising from main magnetic field inhomogeneity and nonlinearities in the applied magnetic field gradients) and of effects arising from the object/patient being imaged. A two stage protocol has been developed to correct both system and object-induced distortion in pelvic images which incorporates measures to maintain the quality, accuracy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 12 publications
0
59
0
Order By: Relevance
“…Our previous work 3 has shown limitations of one such commercial diagnostic phantom to adequately determine distortion across all 3 imaging planes, hence missing regions where patient anatomy may need to be imaged for RTP. A number of studies have developed their own distortion phantoms, for specific applications [24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work 3 has shown limitations of one such commercial diagnostic phantom to adequately determine distortion across all 3 imaging planes, hence missing regions where patient anatomy may need to be imaged for RTP. A number of studies have developed their own distortion phantoms, for specific applications [24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…Two early papers by Schad et al (15,16) discussed the "pincushion" effects seen with 2D phantoms. Subsequent schemes include using a stereotaxic frame as a reference marker (11,14), comparing phantom images from CT and MRI (7,19), and imaging specific MRI phantoms (1,13,17,18) that typically consist of an array of tubes filled with a suitable contrast agent. Mizowaki et al (12) alluded to an important problem with phantom studies: after they assessed the reproducibility of their own phantom-based correction, the authors concluded that such a correction may only be applicable in limited situations.…”
mentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) prosimulation routine, we have chosen 154 Hz/pixel in the vides superior image quality for soft-tissue delineation over frequency encoding direction; therefore, the effects caused computed tomography (CT) and is widely used for target by chemical and susceptibility are considered negligible. and organ delineation in radiotherapy for treatment planning For system-related distortions, we have used gradient dis- (9)(10)(11). The prostate volume on CT appears much larger tortion correction (GDC) software to correct the MRI disthan on MRI (12).…”
Section: Discussionmentioning
confidence: 99%